Comparing Government Activity
XIII, 205 p.
Keywords: The comparative analysis of government activity raises many methodological, theoretical and substantive problems. In this volume authors drawn from varied subfields of political science address some of these problems, including: the usefulness of expenditure data, case interdependence, the issue of non-decision, the measurement of the distribution of power through laws, methodological individualism, cultural explanations, politico-economic interactions, the usefulness of textual analysis and issues of accumulation and aggregation.